2013
DOI: 10.1016/j.devcel.2013.04.015
|View full text |Cite
|
Sign up to set email alerts
|

The BH3-Only SNARE BNip1 Mediates Photoreceptor Apoptosis in Response to Vesicular Fusion Defects

Abstract: Intracellular vesicular transport is important for photoreceptor function and maintenance. However, the mechanism underlying photoreceptor degeneration in response to vesicular transport defects is unknown. Here, we report that photoreceptors undergo apoptosis in a zebrafish β-soluble N-ethylmaleimide-sensitive factor attachment protein (β-SNAP) mutant. β-SNAP cooperates with N-ethylmaleimide-sensitive factor to recycle the SNAP receptor (SNARE), a key component of the membrane fusion machinery, by disassembli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…Indeed, our recent studies demonstrate a marked fragmentation of the Golgi and decreased expression of Golgi-resident proteins such as GBF1 in ␣SNAP-depleted epithelial cells (34 -36). Similarly, a loss of function mutation of the brain-enriched ␤SNAP isoform was shown to trigger Golgi dispersion in zebrafish photoreceptors leading to photoreceptor degeneration (84). Importantly, we observed that Golgi fragmentation by either pharmacologic agents or GBF1 depletion phenocopied all effects of ␣SNAP knockdown on ECM adhesion including impaired processing and mislocalization of ␤1 integrin, decreased expression and phosphorylation of paxillin, and cell detachment (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, our recent studies demonstrate a marked fragmentation of the Golgi and decreased expression of Golgi-resident proteins such as GBF1 in ␣SNAP-depleted epithelial cells (34 -36). Similarly, a loss of function mutation of the brain-enriched ␤SNAP isoform was shown to trigger Golgi dispersion in zebrafish photoreceptors leading to photoreceptor degeneration (84). Importantly, we observed that Golgi fragmentation by either pharmacologic agents or GBF1 depletion phenocopied all effects of ␣SNAP knockdown on ECM adhesion including impaired processing and mislocalization of ␤1 integrin, decreased expression and phosphorylation of paxillin, and cell detachment (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Protein purification and SDS-PAGE were conducted as previously described41. Anti-Pde6c (Abcam; ab5660), zGc325, and histone H3 (Abcam; ab1791) antibodies were used at dilutions of 1:2000, 1:1000 and 1:50000, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…β-SNAP −/− presents photoreceptors degeneration, in which photoreceptors undergo apoptosis in a BH3-only, protein BNip1-dependent mechanism due to failure to disassemble the SNARE. β-SNAP mutant was the first zebrafish mutant to link photoreceptor degeneration to vesicular transport defects [37].…”
Section: Discerning Specific Signaling Pathways Between Cone or Rod Pmentioning
confidence: 99%